They lived to tell the tale (Reader's Digest, 2009)
This book is a collection of 50 thrilling, horrifying, amazing and inspiring stories about men and women who have survived incredible trials of endurance and achieved heroic feats in adversity. It covers recent traumatic events such as 9/11 and 7/7, takes the reader into jungles, volcanoes and the eyes of storms, and ranges back in history through world wars to the early days of polar exploration. The type of story will be familiar to fans of the RD magazine, but what this book does differently is to take each gripping narrative and add photographs, diagrams, maps and other illustrations that take the reader into the heart of the story and enhance their understanding of the extraordinary events. Also included are information boxes that give the reader extra information on the context of the stories, the people involved and the dangers faced.